2022
DOI: 10.23939/mmc2022.04.892
|View full text |Cite
|
Sign up to set email alerts
|

Call warrants pricing formula under mixed-fractional Brownian motion with Merton jump-diffusion

Abstract: Mixed fractional Brownian motion (MFBM) is a linear combination of a Brownian motion and an independent fractional Brownian motion which may overcome the problem of arbitrage, while a jump process in time series is another problem to be address in modeling stock prices. This study models call warrants with MFBM and includes the jump process in its dynamics. The pricing formula for a warrant with mixed-fractional Brownian motion and jump, is obtained via quasi-conditional expectation and risk-neutral valuatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…However, as it will be shown, the transition probability density for stochastic value r(τ ) (16) that is built based on Gaussian measure does not match the solution to the Fokker-Planck equation (18). Let us illustrate this for the case of stochastic equation (16)…”
Section: Stochastic Differential Equation Based On Fbmmentioning
confidence: 99%
See 3 more Smart Citations
“…However, as it will be shown, the transition probability density for stochastic value r(τ ) (16) that is built based on Gaussian measure does not match the solution to the Fokker-Planck equation (18). Let us illustrate this for the case of stochastic equation (16)…”
Section: Stochastic Differential Equation Based On Fbmmentioning
confidence: 99%
“…Based on measure (25), let us build a measure for stochastic process r(τ ) that is given by a stochastic equation (16). For this, we shall use the approach for Brownian motion given in [19,25].…”
Section: Approximation Of Fbm Covariancementioning
confidence: 99%
See 2 more Smart Citations
“…[6] demonstrated that the accuracy of the Black-Scholes model should be improved by including discontinuous jump processes into the conventional stochastic process of geometric Brownian motion (GBM). Notably, [7] pioneered such models for the study of option valuation, and some studies that included jumps in the pricing model are [12][13][14]. Hence, we focused on developing a penalty method for solving a PIDE problem.…”
Section: Introductionmentioning
confidence: 99%